Status of waste-to-energy in Germany, Part I – Waste treatment facilities. (May 2020) - Weber, Kathrin; Quicker, Peter; Hanewinkel, Jörg; Flamme, Sabine
This study gives a detailed overview over the German waste-to-energy sector in 2015. The aim is to quantify the available treatment capacities and the energetic potential of waste in Germany. The work is based on an extensive data collection and evaluation, both from literature sources as well as from a survey among operators of waste treatment plants. The present Part I, gives an overview of all treatment facilities in Germany that convert waste into energy. It was found that in total, almost 320 PJ of end energy are produced in German waste treatment plants: 225 PJ a −1 of heat; and 90 PJ a −1 of electricity. This is a share of about 3.7% of the German end energy consumption.